Pengaruh Motivasi Intrinsik Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Dan Disiplin Kerja Sebagai Variabel Mediasi Pada Badan Pusat Statistik Kabupaten Magelang - Ahmad Taufiq (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2016)
This study proposed to examine and analyze the effect of intrinsic motivation on employee performance, with job satisfaction and work discipline as mediating variable.The object of this study is the office of the Statistics of Magelang regency, and the subject of this study are employees (civil servants) at the Office Statistics of Magelang Regency. The sampling technique in this study is saturated sample. All employees civil servants in BPS Magelang regency totaling 41 people are given a questionnaire.Data from the study were tested and analyzed using the Smart-PLS. The first conclusion is intrinsic motivation significantly influence job satisfaction, and a second conclusion is intrinsic motivation significantly influence the work discipline. The third conclusion is the intrinsic motivation significantly influence performance. The fourth conclusion is job satisfaction does not affect the work discipline, and the fifth conclusion is job satisfaction also has no impact on performance. The sixth conclusion is discipline significantly influence on the performance. The study also concluded that the discipline of work are variables that mediate the relationship between intrinsic motivation to the performance on  the Office Statistics of Magelang regency.